PENGEMBANGAN SOAL FOUR TIER TEST UNTUK MENGETAHUI KONSEPSI ILMIAH SISWA PADA MATERI WUJUD ZAT DAN PERUBAHAN WUJUD ZAT - Irgi Septiadi; Tarmidzi; Nailah Tresnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a valid and reliable Four-Tier Diagnostic Test instrument to identify elementary school students’ scientific conceptions on the topic of states of matter and changes in states of matter. The study was motivated by the high incidence of misconceptions among students and the limited ability of conventional assessments to reveal conceptual understanding in depth. The research employed a Research and Development (R&D) approach consisting of needs analysis, instrument design, item development, expert validation, limited testing, and product evaluation. Data were collected through questionnaires, diagnostic tests, and documentation and analyzed using qualitative and quantitative techniques, including validity, reliability, item difficulty, and discrimination analyses. The validation results indicated that the instrument was feasible for use as a diagnostic assessment. Application of the instrument to 27 elementary school students showed that misconceptions were most prominent in concepts related to evaporation, condensation, and sublimation. The developed instrument can support teachers in identifying students’ conceptual understanding more accurately and in designing more effective remedial instruction.